Arsenic disulfide-triggered apoptosis and erythroid differentiation in myelodysplastic syndrome and acute myeloid leukemia cell lines. Issue 6 (September 2014) - Hu, Xiao-Mei; Yuan, Bo; Tanaka, Sachiko; Song, Min-Min; Onda, Kenji; Tohyama, Kaoru; Zhou, Ai-Xiang; Toyoda, Hiroo; Hirano, Toshihiko
Abstract : Objectives: Effects of arsenic disulfide (As2 S2 ) were investigated by focusing on growth inhibition, apoptosis induction, and erythroid differentiation in MDS-L, F-36p and HL-60 cells, derived from myelodysplastic syndrome (MDS), MDS/acute myeloid leukemia (AML), and de novo AML, respectively. Methods: Cell viability was determined by MTT assay. Apoptosis induction was analyzed using Annexin V/propidium iodide staining. Erythroid differentiation was assessed by the expression level of CD235a, a marker for detection of the erythroid cell lineage. The activation of p38 MAPK and the expression profile of apoptosis-related proteins Bcl-2 and Bid were analyzed using western blot. Results: As2 S2 inhibited cell growth of these cell lines. Of note, the IC50 value of As2 S2 in MDS-L cells was comparable to that in F-36p cells, and was half of that in HL-60 cells. A dose-dependent decrease in cell viability and concomitant increase in the percentage of apoptotic cells were observed in F-36p cells treated with 8 and 16 µM As2 S2 for 72 hours. However, similar phenomena were only observed in HL-60 cells when treated with as high as 16 µM As2 S2 . Furthermore, As2 S2 exerted more potent erythroid differentiation-inducing activity on F-36p cells than HL-60 cells. Interestingly, negative correlation between p38 MAPK signaling pathway and As2 S2 -induced erythroid differentiation was observed in HL-60 cells. Treatment with relatively high concentration of As2 S2 resulted in the downregulation of Bcl-2 and Bid proteins in HL-60 cells. Discussion: These results suggest that compared to AML cell line, MDS and MDS/AML cell lines are more sensitive to not only the erythroid differentiation-inducing activity of As2 S2, but also its cytotoxicity associated with apoptosis induction. These findings further provide novel insight into As2 S2 action toward its use for clinical application in patients with hematological disorders.